Qualitative characteristics of cashmere fiber of Chyangra goat of Nepal - Gorkhali, Neena Amatya; Paudel, Bikash; Basnet, Keshav; Bhandari, Shishir; Pokhrel, Bhoj Raj; Sharma, Surya Bhatta; Sapkota, Saroj (Journal of Nepal Agricultural Research Council, 2023)
This study assesses the different physical characteristics of cashmere fiber quality in Chyangra goats as wax percentage, length of pashmina fiber, fineness (diameter) of fiber obtained from different body parts (neck, belly, and back) in different locations of Mustang district of Nepal. In mid-March to mid-April 2022, cashmere samples were collected from thirty-four unrelated animals. Twenty-two animals were sampled from Upper Mustang and twelve were sampled from Lower Mustang; of which, 22 were male and 12 were female of 1, 2, 3, 4, and greater than 4 years of age. Cashmere fiber length was measured using measuring pad and ruler and fiber diameter was analyzed using the optical projection microscope method. The fixed effect model was used to analyze the least square mean for fiber length, diameter and wax percentage of Chyangra cashmere fiber considering various factors such as location, sex and age. The overall least square mean and standard error for fiber quality parameters namely wax percentage, fiber length and fiber diameter were 9.49±2.2%, 45.97±0.14 mm and 15.36±0.19 µm respectively. Even though there is a significant difference in the considered parameters by location, the fineness and length of the fiber of both locations was within the finest fiber ranging from 13-16 µm diameter and more than 40 mm length. The present study has evidenced that Chyangra goat of Nepal can be characterized as one of the finest Cashmere goats however some management steps must be taken to improve the quality (cleanliness) of fiber and the volume of fiber production. Significant differences were found in location, sex, and trend of difference in age of the animals indicating the potential to improve cashmere quality by adopting proper management and selection methods through selection of goats with larger body size and confirmation to obtain more quantity of fiber per animal.